Comprehensive Metabolite Profiling of Cinnamon (Cinnamomum zeylanicum) Leaf Oil Using LC-HR/MS, GC/MS, and GC-FID: Determination of Antiglaucoma, Antioxidant, Anticholinergic, and Antidiabetic Profiles - Mutlu, Muzaffer; Bingol, Zeynebe; Uc, Eda Mehtap; Koksal, Ekrem; Goren, Ahmet C.; Alwasel, Saleh H.; Gulcin, Ilhami (Mdpi, 2023)
In this study, for the first time, the antioxidant and antidiabetic properties of the essential oil from cinnamon (Cinnamomum zeylanicum) leaves were evaluated and investigated using various bioanalytical methods. In addition, the inhibitory effects of cinnamon oil on carbonic anhydrase II (hCA II), acetylcholinesterase (AChE), and alpha-amylase, which are associated with various metabolic diseases, were determined. Further, the phenolic contents of the essential oil were determined using LC-HRMS chromatography. Twenty-seven phenolic molecules were detected in cinnamon oil. Moreover, the amount and chemical profile of the essential oils present in cinnamon oil was determined using GC/MS and GC-FID analyses. (E)-cinnamaldehyde (72.98%), benzyl benzoate (4.01%), and trans-Cinnamyl acetate (3.36%) were the most common essential oils in cinnamon leaf oil. The radical scavenging activities of cinnamon oil were investigated using 1,1-diphenyl-2-picryl-hydrazil (DPPH center dot), 2,2 '-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid), and (ABTS(center dot+)) bioanalytical scavenging methods, which revealed its strong radical scavenging abilities (DPPH center dot, IC50: 4.78 mu g/mL; and ABTS(center dot+), IC50: 5.21 mu g/mL). Similarly, the reducing capacities for iron (Fe3+), copper (Cu2+), and Fe3+-2,4,6-tri(2-pyridyl)-S-triazine (TPTZ) were investigated. Cinnamon oil also exhibited highly effective inhibition against hCA II (IC50: 243.24 mu g/mL), AChE (IC50: 16.03 mu g/mL), and alpha-amylase (IC50: 7.54 mu g/mL). This multidisciplinary study will be useful and pave the way for further studies for the determination of antioxidant properties and enzyme inhibition profiles of medically and industrially important plants and their oils.
Keywords: Cinnamomum zeylanicum; polyphenol; cinnamon oil; antioxidant activity; LC-HRMS; GCMS; enzyme inhibition